2017
DOI: 10.1016/j.clim.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and autoimmunity

Abstract: Autophagy is a highly conserved protein degradation pathway from yeasts to humans that is essential for removing protein aggregates and misfolded proteins in healthy cells. Recently, autophagy-related genes polymorphisms have been implicated in several autoimmune diseases including systemic lupus erythematosus, rheumatoid arthritis, psoriasis, and multiple sclerosis. Numerous studies reveal autophagy and autophagy-related proteins also participate in immune regulation. Conditional deletions of autophagy-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(68 citation statements)
references
References 93 publications
1
65
0
1
Order By: Relevance
“…These findings are in agreement with other studies that show WDFY3 is dispensable for starvation-induced autophagy [11]. WDFY3 targets specifically ubiquitinated protein aggregates in selective autophagy and has not been shown to play a role in other type of autophagy pathways such as LC3-associated phagocytosis [27]. …”
Section: Discussionsupporting
confidence: 92%
“…These findings are in agreement with other studies that show WDFY3 is dispensable for starvation-induced autophagy [11]. WDFY3 targets specifically ubiquitinated protein aggregates in selective autophagy and has not been shown to play a role in other type of autophagy pathways such as LC3-associated phagocytosis [27]. …”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have mainly focused on the muscular microenvironment ( 33 35 ); research on peripheral blood immune cells is lacking. T-cell homeostasis is disrupted in autoimmune diseases, including SLE and RA ( 36 , 37 ). Recent immunohistochemical studies on muscle biopsies from our laboratory and others have also demonstrated that T lymphocytes often infiltrate muscle fiber in PM/DM ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The detailed interaction between inflammasomes and autophagy is beyond the scope of the article and described somewhere else . Autophagy and autophagy‐related gene polymorphisms are involved in various autoimmune diseases including IBD, SLE, RA, psoriasis, and MS . Genome‐wide association studies have shown an association between autophagy‐related gene 5 with SLE .…”
Section: Negative Regulation Of Cgas‐sting Signaling and Its Impact Omentioning
confidence: 99%